Parish Futsal: A Technical–Educational or Pastoral Challenge? Notes on a Multiple-Case Study in Rome - Macale, Carlo (Religions, 2024)
This article aims to present a multiple-case study of parish sports clubs affiliated with the Centro Sportivo Italiano (a Catholic-inspired sports promotion body), present in the Rome area. The purpose of this research is to explore whether there is a relationship between futsal activities and the parish pastoral project. It was a qualitative study that, after listening to key informants, conducted group interviews with some coaches (13) of the teams linked to the parish. This research brought out what the elements of distance between the sports groups and the parish community are, as well as what the strengths may be for the integration of the sports education project within a pastoral dynamic. Two lines of interpretation of the data in pedagogical-improvement terms were also provided: one of a deductive nature and one of a hermeneutic nature.